Survivor and other reality T.V. gameshows: the uses and gratifications perspective on a reality sub-genre - Mead, James A. (My University, 2006)
Ever since the 1930s when different forms of media such as film, radio, and print became a main source/influence of how people obtained information and were entertained, media theorists have questioned the effects of the technology. Early research studies determined that an audience member actively selected media content that best served (gratified) his/her personal interests. Extensions of this research led to the development of Uses and Gratifications Theory. The most recent of these studies focused specifically on determining the top viewing motivations of particular television genres (i.e. soap opera and reality). These findings not only indicated that the top motives varied from one genre to another, but also revealed that additional motives exist in television viewing that had not previously been discussed. The current fan-favorite reality genre needs additional attention in terms of viewing motivations because several sub-genres exist from within. To date, little research has been done linking reality television to uses and gratifications, and none has been found that explore the potential of varying motives between the reality sub-genres. Literature research into the history of television along with the reality genre and its sub-genres (particularly gamedocs) was done in order to create a survey for determining top motivations into specific television viewing. In addition, a qualitative analysis of Survivor, one of the most popular gamedoc reality programs on the air, was done to assist in creation of the survey. Undergraduate students ranging in age from 18-25 years old from three universities throughout the United States were asked to participate in this survey that intended on answering three research questions pertaining to the motivations into gamedoc reality programs. The first question involved determining the percentage of respondents who actually view at least one hour of gamedoc programming per week. Respondents were asked to indicate whether or not they watch such gamedoc shows as Survivor, Big Brother, and Fear Factor. The second question attempted to determine the top motives for watching gamedocs. Participants were provided with a list of potential reasons for why one might watch gamedocs, and then asked to rate how likely they would be to watch for each specific reason. The final question sought to determine what differences, if any, exist in the top motives for viewing reality gamedocs with regards to the gender of the respondent. Results indicated that the 61 percent of the sample do seek out gamedocs for some form of personal fulfillment. Both genders tended to agree on many of the top motives for watching: they found the content somewhat humorous, even laughable at times, they found them generally entertaining, and were intrigued by the week-by-week happenings that occurred within a particular program. Despite the similarities, it was determined that 9 out of the 19 motives were significantly different in the mean scores between males and females. Furthermore, it was found that males watched more television in general, while females watched more reality gamedocs. Females also tended to get more from watching gamedocs, as they consistently ranked the motives higher than males. Findings of this study add reliability to past research into uses and gratifications, and suggest that motives of television viewing may vary from genre to genre. In order to further determine that hypothesis, similar research will have to be done with other reality sub-genres.
This file was last viewed in Adobe Reader 7.0
Keywords: Survivor (Television program); Reality television programs; Television viewers -- Psychology.